Surface Plasmon Resonance: An Introduction to a Surface Spectroscopy Technique - Tang, Yijun (2010)
Surface plasmon resonance (SPR) has become an important optical biosensing technology in the areas of biochemistry, biology, and medical sciences because of its real-time, label-free, and noninvasive nature. The high cost of commercial devices and consumables has prevented SPR from being introduced in the undergraduate laboratory. Here we present an affordable homemade SPR device with all of its components accessible to visualization. This design allows ease of integration with electrochemistry and makes the device suitable for education. We describe a laboratory experiment in which students examine the relationship between the SPR angle and the solution refractive index at the interface and perform a coupled SPR–electrochemistry experiment. Students also study the antibody–antigen binding activity. Most of the experimental work was done as a project by a grade 12 high-school student under proper supervision. We believe that the SPR device and the SPR laboratory will enhance undergraduate chemical education by introducing students to this important modern instrumentation and will help students to learn and understand the molecular interactions occurring at interfaces.